Telemedicine in French memory clinics during Covid‐19 crisis. (1st February 2022) - Morin, Alexandre; Pressat‐Laffouilhere, Thibault; Sarazin, Marie; Lagarde, Julien; Roue‐Jagot, Carole; Paquet, Claire; Cognat, Emmanuel; Dumurgier, Julien; Pasquier, Florence; Lebouvier, Thibaud; Ceccaldi, Mathieu; Godefroy, Olivier; et al.
Abstract: Background: In early 2020, COVID‐19 outbreak struck France leading to a national lockdown between March 17 th and May 11 th . While standard in‐person medical consultation was complicated, telemedicine dramatically expanded. In order to evaluate the impact of this unpreceded situation on clinical practice and use of psychoactive drug in dementia care, we conducted a nationwide clinical prospective and retrospective study. Method: During the lockdown period, telemedicine patients' demographic and clinical data were retrospectively collected from 7 French memory clinics (telemedicine cohort). Clinical diagnoses, treatment changes, cognitive modifications since last consultations and living conditions during the lockdown were systematically retrieved. In Rouen site, we also included patients only reached by a secretary to propose a postponed visit after lockdown (no‐telemedicine cohort) and patients seen in 2019 during the same period of the year (Rouen‐2019). The primary outcome was any change in psychoactive drug and a specific analysis on sedative treatment increase was the secondary outcome, defined as any increase in the prescriptions of antipsychotics or benzodiazepines. Result: The telemedicine cohort included 874 patients (73 from Rouen), while no‐telemedicine control cohort and Rouen‐2019 cohorts included respectively 86 and 234 patients (table 1). In the telemedicine cohort, treatments were modified for 10.7% of the patients with more treatment modification among the patients living with a relative (+5.8% (CI95% [0.2%; 11.4%] p=0.04) and among the patients with Alzheimer's disease (+12.2% (CI95% [7.1%; 17.3%] p<0.001). When comparing therapeutic strategies in 2020 and 2019 for Rouen site, 24.6% of the patients had their treatment modified in 2020 and 12.4% in 2019. That difference was however not statically significant with an adjusted percentage difference of ‐4% (CI95% [‐10.8%; 3.4%] p=0.27, including the telemedicine and no‐telemedicine cohorts for 2020. Conclusion: Telemedicine seems to have had only minor negative impacts on clinical practice in memory clinics.